THE EFFECT OF THE NUMBER OF INDUSTRIAL COMPANIES, INVESTMENTS AND THE ECONOMIC CRISIS ON THE REALIZATION OF LABOR ABSORPTION IN THE MIDDLE MEDIUM TEXTILE - Fauziah, Ilma Nur; Mukhtar, Saparuddin; Nurjanah, Siti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the effect of the number of industrial companies, investment and economic crisis on the realization of labor absorption in the large and medium-sized textile industry sector in East Java Province. This study uses a multiple linear regression method with the Ordinary Least Square (OLS) model. This study uses secondary data which includes employment, the number of industrial companies and investment, while the economic crisis is included in the category of dummy variables. The results of this study indicate that the number of industrial and investment companies has a positive and significant effect on employment. Meanwhile, the economic crisis has a negative and insignificant effect on the realization of employment in the mediumlarge textile industry sector in East Java Province.